Accessory Genomic Epidemiology of Cocirculating Acinetobacter baumannii Clones - Valeria Mateo-Estrada (American Society for Microbiology, 2021)
Whole-genome sequencing for epidemiological investigations (genomic epidemiology) has been of paramount importance to understand the transmission dynamics of many bacterial (and nonbacterial) pathogens. Commonly, variation in the core genome, single nucleotide polymorphisms (SNPs), is employed to carry out genomic epidemiology.